Organization And Planning Of Circle Work In Professional Education - A.T.Umirov (Academia One Publishing, 2024)
education of economic, physical, moral, national culture,education of conscious discipline,education of relations of care of society and the property of the individual,formation of economic, professional, moral, artistic, national, physical labor, profetsinal culture,curriculum, DTS, curriculum, lesson plan, non-traditional lesson technology, text of a lecture, preparation for activities of a calendar topic plan, preparation for the academic year.
Keywords: professional; plan; education; method